Negative electrode material, preparation method thereof and battery

By using nitrogen-doped amorphous carbon material in the negative electrode material and combining ordered and disordered structures, the problems of lithium ion co-embedding and SEI film in the prior art are solved, and the improvement of high capacity, high head efficiency, high temperature performance and fast charging performance are achieved.

CN119650607APending Publication Date: 2025-03-18BTR NEW MATERIAL GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311199776.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the charging and discharging process of existing negative electrode materials, it is easy to co-embed solvated lithium ions, and it is difficult to form a uniform SEI film on the surface, which affects the battery's capacity life, fast charging and other performance.

Method used

Nitrogen doped amorphous carbon materials are used to combine ordered structures and disordered structures. By controlling the disorder of amorphous carbon materials, lithium ion transport channels are increased and the interaction between the material and lithium ions is enhanced.

Benefits of technology

It improves the fast charging performance of the negative electrode material, takes into account high capacity, high first-time efficiency and high temperature performance, and enhances the high-temperature cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650607A_ABST
    Figure CN119650607A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material and a preparation method thereof, and a battery, the negative electrode material comprises an inner core and an amorphous carbon material located on at least part of the surface of the inner core, the inner core comprises graphite, and the amorphous carbon material comprises an ordered structure and a disordered structure; wherein the disorder degree of the amorphous carbon material is 0.05 to 0.8. According to the negative electrode material and the preparation method thereof provided by the invention, the nitrogen-doped amorphous carbon material in the negative electrode material can have high conductivity of ordered structure carbon and high lithium ion transmission performance of disordered structure carbon, and has relatively strong interaction with lithium ions, so that the negative electrode material has high capacity, high first efficiency and high temperature performance; and the fast charging performance of the negative electrode material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of negative electrode materials, and in particular, to negative electrode materials and preparation methods thereof, and batteries. Background Art

[0002] Graphite is one of the main raw materials for lithium-ion batteries. It has the advantages of high capacity, high compaction, environmental friendliness and low price, and is widely used in 3C, power tools and other fields. As the negative electrode material, graphite has poor compatibility with electrolytes, solvated lithium ions are easily co-embedded during charging and discharging, and it is difficult to form a uniform SEI film on the surface, which greatly affects the battery's capacity, life, and fast charging performance. In order to improve the comprehensive performance of the material, the negative electrode material usually needs to be coated with a layer of amorphous carbon on the surface.

[0003] The current coating amount of amorphous carbon is usually above 1%. A higher carbon coating amount can easily cause the loss of specific capacity, initial efficiency and high temperature performance of the negative electrode material. The more common amorphous carbon formed by asphalt coating carbonization is mainly soft carbon. Compared with hard carbon, soft carbon has better conductivity, but the interlayer spacing of carbon layers is smaller, and the lithium ion transmission capacity is slightly lower than that of hard carbon. The amorphous carbon formed by carbonization of resin coating materials is mainly hard carbon. Although the hardness is conducive to the transmission of lithium ions, the bonding ability with graphite is poor, and the conductivity is not as good as soft carbon. Hard carbon coating will also increase the impedance of the negative electrode material surface. It can be seen that it is still difficult for negative electrode materials to take into account capacity, fast charging performance and high temperature performance at the same time. Summary of the invention

[0004] In view of this, the present application provides a negative electrode material, a preparation method thereof, and a battery. The nitrogen-doped amorphous carbon material in the negative electrode material includes a disordered structure and an ordered structure, so that the negative electrode material can have both the high conductivity of ordered structure carbon and the high lithium ion transmission performance of disordered structure carbon, and has a strong interaction with lithium ions. The negative electrode material takes into account high capacity, high initial efficiency, and high temperature performance, and further improves the fast charging performance of the negative electrode material.

[0005] In a first aspect, the present application provides a negative electrode material, comprising a core and an amorphous carbon material located on at least a portion of the surface of the core, wherein the core comprises graphite, and the amorphous carbon material comprises an ordered structure and a disordered structure; wherein the disorder degree of the amorphous carbon material is 0.05 to 0.8;

[0006] The disorder degree of the amorphous carbon material is obtained by the following test method:

[0007] The amorphous carbon material was observed by high-resolution transmission electron microscopy. Ten points of amorphous carbon material with a length of 100 nm parallel to the particle surface were randomly selected on the surface of the negative electrode material, and the lengths of the disordered structures therein were measured, which were recorded as: n1, n2, n3...n10 respectively. The calculation formula for the degree of disorder w is: w=(n1 / 100+n2 / 100+n3 / 100+...+n10 / 100) / 10.

[0008] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite.

[0009] In some embodiments, the median particle size of the graphite is 5 μm to 10 μm.

[0010] In some embodiments, the amorphous carbon material includes doping nitrogen.

[0011] In some embodiments, the amorphous carbon material includes doped nitrogen, and the mass content of the doped nitrogen in the amorphous carbon material is 0.01% to 0.2%.

[0012] In some embodiments, the amorphous carbon material is located on the surface of the graphite to form a carbon coating layer, and the thickness of the carbon coating layer is 5 nm to 50 nm.

[0013] In some embodiments, the negative electrode material is measured by Raman spectroscopy at 1300 cm -1 ~1350cm -1 The peak area of ​​the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak within the range is I D / I G , 0.6≤I D / I G ≤1.0.

[0014] In some embodiments, the median particle size of the negative electrode material is 5 μm to 10 μm.

[0015] In some embodiments, the specific surface area of ​​the negative electrode material is 0.2 m 2 / g~3m 2 / g.

[0016] In some embodiments, the tap density of the negative electrode material is 0.7 g / cm 3 ~1.2g / cm 3 .

[0017] In some embodiments, the compaction density of the negative electrode material at 5T pressure is 1.6 g / cm 3 ~2.0g / cm 3.

[0018] In some embodiments, the mass percentage content of the amorphous carbon material in the negative electrode material is 0.05% to 0.3%.

[0019] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0020] Adding graphite into a coating liquid for mixing and dispersion, and drying to obtain a mixture, wherein the coating liquid comprises solid asphalt with a softening point of ≥180°C, an organic solvent, and a polyamine compound;

[0021] placing the mixture in an oxidizing atmosphere for pre-oxidation treatment to obtain a precursor;

[0022] The precursor is carbonized to obtain a negative electrode material.

[0023] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite.

[0024] In some embodiments, the median particle size of the graphite is 5 μm to 10 μm.

[0025] In some embodiments, the mass content of carbon in the graphite is ≥ 95%.

[0026] In some embodiments, the coking value of the solid asphalt is 40% to 70%.

[0027] In some embodiments, the organic solvent includes one of tetrahydrofuran, quinoline, toluene, xylene, N-methylpyrrolidone and ethanol.

[0028] In some embodiments, the mass ratio of the graphite, the solid asphalt, the organic solvent and the polyamine compound is 100:(0.1-1):(50-500):(0.01-0.4).

[0029] In some embodiments, the polyamine compound includes at least one of polyetheramine, polyethyleneamine, polyethyleneimine, polyurethane, polyamide, polyacrylamide and polyimide.

[0030] In some embodiments, the solid asphalt includes at least one of petroleum-based solid asphalt and coal-based solid asphalt.

[0031] In some embodiments, the mixing and dispersing method includes at least one of mechanical stirring and ultrasonic dispersion.

[0032] In some embodiments, the drying process is performed at a temperature greater than the boiling point of the organic solvent.

[0033] In some embodiments, the drying temperature is greater than the boiling point of the organic solvent, and the difference is 5°C to 10°C.

[0034] In some embodiments, the drying process is performed under stirring.

[0035] In some embodiments, the pre-oxidation treatment is performed in a rotary kiln, and the rotation speed of the rotary kiln is 2 rpm to 20 rpm.

[0036] In some embodiments, the oxidizing atmosphere includes air or oxygen.

[0037] In some embodiments, the gas flow rate of the oxidizing atmosphere is controlled to be 100 mL / min to 1000 mL / min.

[0038] In some embodiments, the pre-oxidation treatment is performed at a temperature of 200°C to 400°C.

[0039] In some embodiments, the heating rate of the pre-oxidation treatment is 0.5° C. / min to 2.0° C. / min.

[0040] In some embodiments, the pre-oxidation treatment is carried out for a holding time of 1 h to 5 h.

[0041] In some embodiments, the carbonization process is performed under a protective atmosphere.

[0042] In some embodiments, the carbonization process is performed under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.

[0043] In some embodiments, the temperature of the carbonization treatment is 800°C to 1500°C.

[0044] In some embodiments, the heating rate of the carbonization treatment is 0.5°C / min to 5.0°C / min.

[0045] In some embodiments, the carbonization treatment is carried out for a holding time of 1 h to 10 h.

[0046] The technical solution of this application has at least the following beneficial effects:

[0047] In the negative electrode material provided in the present application, the negative electrode material includes graphite and amorphous carbon material, the amorphous carbon material includes an ordered structure and a disordered structure, wherein the degree of disorder of the amorphous carbon material is 0.05 to 0.8; by controlling the degree of disorder in the amorphous carbon material, while ensuring the electronic conductivity of the material surface, the lithium ion transmission channel is increased and the interaction between the material and lithium ions is enhanced, thereby accelerating the desolvation process and transmission of lithium ions during the charging process, thereby improving the fast charging performance of the material.

[0048] The preparation method of the negative electrode material provided in the present application is as follows: the coating liquid containing solid asphalt, organic solvent and polyamine compound is fully mixed with graphite, and the organic solvent is removed before pre-oxidation treatment. The pre-oxidation treatment can accelerate the chemical crosslinking between the polyamine compound and the asphalt molecules and between the asphalt molecules. At the same time, the pre-oxidation can reduce the deterioration of the high-temperature cycle performance caused by excessive pores and non-density of the amorphous carbon caused by direct carbonization. After carbonization treatment, the introduction of oxygen-containing bodies and amino groups in the polyamine compound can promote the transformation of part of the structure of the amorphous carbon material after carbonization into a disordered structure with higher disorder and larger interlayer spacing. This nitrogen-doped ordered-disordered interphase structure increases the lithium ion transmission channel and enhances the interaction between the material and lithium ions while ensuring the electronic conductivity of the material surface, accelerates the desolvation process and transmission of lithium ions during charging, thereby improving the fast charging performance of the material. In addition, the pre-oxidation treatment increases the density of the amorphous carbon coating layer, further improving the high-temperature cycle stability of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 A schematic diagram of the structure of the negative electrode material provided in the embodiment of the present application;

[0050] Figure 2 A schematic diagram of a process for preparing a negative electrode material provided in an embodiment of the present application;

[0051] Figure 3a A high-resolution transmission electron microscope image of the negative electrode material provided in Example 1 of the present application;

[0052] Figure 3b This is a high-resolution transmission electron microscopy image of the negative electrode material provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0053] In order to better illustrate the present application and facilitate understanding of the technical solution of the present application, the present application is further described in detail below. However, the following embodiments are only simple examples of the present application and do not represent or limit the scope of protection of the present application. The scope of protection of the present application shall be subject to the claims.

[0054] In a first aspect, the present application provides a negative electrode material, such as Figure 1 As shown, the negative electrode material includes a core and an amorphous carbon material located on at least a portion of the surface of the core, the core includes graphite, and the amorphous carbon material includes an ordered structure and a disordered structure; wherein the disorder degree of the amorphous carbon material is 0.05 to 0.8;

[0055] The disorder degree of the amorphous carbon material is obtained by the following test method:

[0056] The amorphous carbon material was observed by high-resolution transmission electron microscopy. Ten points of amorphous carbon material with a length of 100 nm parallel to the particle surface were randomly selected on the surface of the negative electrode material, and the lengths of the disordered structures therein were measured, which were recorded as: n1, n2, n3...n10, respectively. The calculation formula for the degree of disorder w is: w=(n1 / 100+n2 / 100+n3 / 100+...+n10 / 100) / 10.

[0057] In the negative electrode material provided in the present application, the negative electrode material includes graphite and amorphous carbon material, the amorphous carbon material includes an ordered structure and a disordered structure, wherein the degree of disorder of the amorphous carbon material is 0.05 to 0.8; by controlling the degree of disorder in the amorphous carbon material, while ensuring the electronic conductivity of the material surface, the lithium ion transmission channel is increased and the interaction between the negative electrode material and lithium ions is enhanced, the desolvation process and transmission of lithium ions during the charging process are accelerated, thereby improving the fast charging performance of the material.

[0058] Specifically, the disorder degree of the amorphous carbon material can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.7 or 0.8, etc., which is not limited here.

[0059] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite.

[0060] Natural graphite is usually formed by regional metamorphism of sedimentary rocks rich in organic matter or carbon. According to different crystal forms, natural graphite is divided into three categories in industry: dense crystalline graphite, flake graphite and cryptocrystalline graphite.

[0061] Artificial graphite is a graphite material obtained by carbonizing organic matter and then undergoing high-temperature graphitization treatment.

[0062] In some embodiments, natural flake graphite is spheroidized to obtain spherical graphite.

[0063] In some embodiments, the median particle size of graphite is 5 μm to 10 μm, more specifically, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. After many tests, it was found that the median particle size of graphite was controlled within the above range, which was beneficial for graphite to take into account processing performance, capacity and rate performance.

[0064] In some embodiments, the mass content of carbon in the graphite is ≥ 95%, specifically 95%, 96%, 97%, 97.5%, 98.3%, 98.8% or 99%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the mass content of carbon in the graphite is ≥ 99.95%.

[0065] In some embodiments, the amorphous carbon material contains nitrogen. It can be understood that the nitrogen doped in the ordered and disordered interphase structure of the amorphous carbon material can increase the lithium ion transmission channel and enhance the interaction between the negative electrode material and the lithium ions while ensuring the electronic conductivity of the material surface.

[0066] In some embodiments, the mass content of the doped nitrogen element in the negative electrode material is 0.01% to 0.2%, specifically 0.01%, 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18% or 0.2%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. An appropriate amount of doped nitrogen element can improve the electronic conductivity of the carbon material and the interaction between it and lithium ions, and promote the transmission of electrons and lithium ions.

[0067] In some embodiments, the negative electrode material is measured by Raman spectroscopy at 1300 cm -1 ~1350cm -1 The peak area of ​​the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak within the range is I D / I G , 0.6≤I D / I G ≤1.0; specifically, it may be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 1.0, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0068] It can be understood that the Raman spectrum D band (1300 cm -1 ~1350cm-1 ) reflects the disordered structure and defect structure of carbon materials. The G band (1500cm -1 ~1580cm -1 ) and the sp 2 It is related to the vibration of bonded carbon atoms, reflecting the ordered structure of carbon materials. D / I G The area ratio reflects the proportion of disordered structure and ordered structure of carbon materials.

[0069] In some embodiments, the specific surface area of ​​the negative electrode material is 0.2 m 2 / g~3m 2 / g; specifically, it can be 0.2m 2 / g, 0.3m 2 / g, 0.5m 2 / g, 1.0m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.1m 2 / g, 2.3m 2 / g, 2.5m 2 / g, 2.8m 2 / g or 3m 2 / g, etc., and of course, it can also be other numbers within the above range, which is not limited here. The inventors have found through multiple experiments that controlling the specific surface area of ​​the negative electrode material within the above range is conducive to improving the initial efficiency and cycle performance of the lithium battery made of the negative electrode material.

[0070] In some embodiments, the tap density of the negative electrode material is 0.7 g / cm 3 ~1.2g / cm 3 ; Specifically, it can be 0.7g / cm 3 , 0.75g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 , 1.0g / cm 3 or 1.2g / cm 3 The above range is not limited to the listed values, and other values ​​not listed within the above range are also applicable.

[0071] In some embodiments, the compaction density of the negative electrode material at 5T pressure is 1.6 g / cm 3 ~2.0g / cm 3 ; Specifically, it can be 1.6g / cm 3 , 1.65g / cm 3, 1.7g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 or 2.0g / cm 3 The above range is not limited to the listed values, and other values ​​not listed within the above range are also applicable.

[0072] In some embodiments, the amorphous carbon material is located on the surface of the graphite to form a carbon coating layer, and the thickness of the carbon coating layer is 5nm to 50nm, specifically 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm, etc., which is not limited here.

[0073] In some embodiments, the mass percentage content of the amorphous carbon material in the negative electrode material is 0.1% to 0.3%, specifically 0.1%, 0.12%, 0.13%, 0.15%, 0.17%, 0.19%, 0.2%, 0.22%, 0.25%, 0.28% or 0.3%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Due to the low coating amount of the surface amorphous carbon material, the distance that lithium ions pass through the carbon material coating layer to reach the graphite is shortened, which is more conducive to the transmission of ions. At the same time, due to the low coating amount, the loss of capacity and first effect caused by the amorphous carbon material in the coating layer is reduced, and the high temperature performance of the material is improved.

[0074] In some embodiments, the median particle size of the negative electrode material is 5 μm to 10 μm, specifically, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm, etc., which is not limited here.

[0075] Second, as Figure 2 As shown, the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0076] S10, adding graphite to a coating liquid for mixing and dispersing, and drying to obtain a mixture, wherein the coating liquid comprises solid asphalt having a softening point ≥ 180° C., an organic solvent, and a polyamine compound;

[0077] S20, placing the mixture in an oxidizing atmosphere for pre-oxidation treatment to obtain a precursor;

[0078] S30, carbonizing the precursor to obtain a negative electrode material.

[0079] The preparation method of the negative electrode material provided in the present application comprises the following steps: fully mixing a coating liquid containing solid asphalt, an organic solvent and a polyamine compound with graphite, and performing a pre-oxidation treatment after removing the organic solvent. The pre-oxidation treatment can accelerate the chemical crosslinking between the polyamine compound and the asphalt molecules and between the asphalt molecules. After carbonization treatment, the introduction of oxygen-containing groups and amino groups in the polyamine compound can promote the transformation of part of the structure of the carbon material after carbonization into a disordered structure with higher disorder and larger interlayer spacing, and realizes a certain degree of nitrogen doping. This nitrogen-doped ordered-disordered interphase structure increases the lithium ion transmission channel and enhances the interaction between the material and lithium ions while ensuring the electronic conductivity of the material surface, accelerates the desolvation process and transmission of lithium ions during charging, and thus improves the fast charging performance of the material.

[0080] The following is a detailed description of the preparation method provided in this scheme:

[0081] Before step S10, the preparation method further includes:

[0082] The natural flake graphite is shaped to obtain spherical graphite.

[0083] Natural flake graphite is natural crystalline graphite. It is shaped like fish phosphate, belongs to the hexagonal crystal system, and has a layered structure. It has good high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, and acid and alkali resistance.

[0084] In some embodiments, the shaping comprises at least one of pulverizing, spheronizing or classifying.

[0085] The natural graphite can be shaped by spheroidization, with the spheroidization rate controlled at 500r / min to 5000r / min and the spheroidization time at 0.2 to 10h.

[0086] The median particle size of the graphite obtained by shaping is 5μm to 20μm, more specifically, it can be 5μm, 8μm, 9μm, 10μm, 11μm, 12μm, 14μm, 15μm, 16μm, 19μm or 20μm, etc., but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. After many tests, it was found that the median particle size of graphite is controlled within the above range, which is beneficial to take into account processing performance, capacity and rate performance. Preferably, the median particle size of graphite is 6μm to 15μm.

[0087] In some embodiments, the graphite may also be artificial graphite.

[0088] In some embodiments, the mass content of carbon in the graphite is ≥95%, specifically 95%, 96%, 97%, 97.5%, 98.3%, 98.8% or 99%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0089] Before step S10, the method further includes:

[0090] The solid asphalt with a softening point of ≥180°C, an organic solvent and a polyamine compound are fully mixed to obtain a coating liquid.

[0091] In some embodiments, the organic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, tetrahydrofuran, and dichloromethane.

[0092] In some embodiments, the solid asphalt with a softening point ≥ 180° C. includes at least one of petroleum-based solid asphalt and coal-based solid asphalt.

[0093] In some embodiments, the polyamine compound includes at least one of polyetheramine, polyethyleneamine, polyethyleneimine, polyurethane, polyamide, polyacrylamide and polyimide.

[0094] In some embodiments, the mass ratio of the solid asphalt, the organic solvent and the polyamine compound is (0.1-1): (50-500): (0.01-0.4), specifically 0.1:50:0.01, 0.1:50:0.05, 0.2:100:0.05, 0.3:150:0.1, 0.5:200:0.2, 0.8:250:0.3, 0.8:300:0.25, 1:400:0.3 or 1:500:0.4, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable. If the amount of polyamine compounds added is too low, the disorder and nitrogen doping of the coating layer will be reduced, and the improvement of the fast charging performance of the material will be limited. However, if the amount of polyamine compounds added is too high, more pores will be generated in the coating layer during the coating carbonization process, which will increase the surface defects and the specific surface area, greatly reduce the initial efficiency of the material, and increase the side reactions during the high-temperature cycle of the battery, and the high-temperature cycle performance will deteriorate. Therefore, controlling the amount of polyamine compounds added can make the negative electrode material take into account high capacity, high initial efficiency, and high-temperature performance, and further improve the fast charging performance of the negative electrode material.

[0095] In some embodiments, the mixing and dispersing method includes at least one of mechanical stirring and ultrasonic dispersion. When mechanical stirring is used for mixing, a propeller stirrer, a turbine stirrer, a flat paddle stirrer, etc. can be used, as long as the components in the modifier are fully mixed and uniform.

[0096] Stirring can be carried out at room temperature or in a preheated state. Preferably, the stirring temperature can be controlled at 20°C to 80°C. It can be understood that appropriate preheating is beneficial for the organic solvent to fully dissolve and dilute the solid asphalt, so that the saturated components, aromatic components, gums and asphaltenes in the solid asphalt are fully dispersed, which is beneficial for the mixing of various components to form a uniform liquid.

[0097] S10, adding graphite into the coating liquid for mixing and dispersion, and drying to obtain a mixture.

[0098] In some embodiments, the mass ratio of the graphite to the solid asphalt is 100:(0.1-1), specifically 100:0.1, 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8 or 100:1, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Too much or too little solid asphalt will reduce the capacity and first efficiency of the composite material.

[0099] The liquid phase coating process can achieve uniform coating at a low coating amount. Compared with solid phase mixed coating, liquid phase coating can reduce the content of coating material (carbon material) to 0.1% to 0.3% and ensure the uniformity of coating.

[0100] In some embodiments, graphite is added to the coating liquid and fully mixed and dispersed to form a mixed liquid, and the mixing method includes at least one of mechanical stirring and ultrasonic dispersion.

[0101] When mechanical stirring is used for mixing, a propeller stirrer, a turbine stirrer, a flat paddle stirrer, etc. can be used, as long as the components in the mixture are fully mixed and uniform. The stirring can be carried out at room temperature.

[0102] In some embodiments, the stirring rate is 10 r / min to 1000 r / min, specifically 10 r / min, 50 r / min, 70 r / min, 100 r / min, 120 r / min, 150 r / min, 200 r / min, 300 r / min, 350 r / min, 400 r / min, 500 r / min or 1000 r / min, etc., which are not limited here. Stirring will make the mixing of the conductive agent, graphite and modifier more uniform, but too slow stirring speed will lead to low uniformity of the mixture, so that the conductive agent dispersion uniformity of the final negative electrode material is poor; but too fast stirring speed will have higher requirements on equipment and increase costs.

[0103] In some embodiments, the drying temperature is greater than the boiling point of the organic solvent, and the difference is 5° C. to 10° C. The drying method may be, for example, oven drying, stirring evaporation, spray drying, etc. The drying process in this embodiment can remove the organic solvent in the mixture as much as possible.

[0104] In some embodiments, the drying treatment method is stirring evaporation, and the stirring evaporation device is equipped with a condensation recovery device. Through the condensation recovery device, the solvent can be recycled, which greatly reduces the amount of solvent used and reduces production costs.

[0105] In some embodiments, the drying process is performed under stirring.

[0106] S30, placing the mixture in an oxidizing atmosphere for pre-oxidation treatment to obtain a precursor;

[0107] In some embodiments, the pre-oxidation treatment is carried out in a rotary kiln, and the rotation speed of the rotary kiln is 2rpm to 20rpm, specifically 2rpm, 4rpm, 5rpm, 8rpm, 10rpm, 12rpm, 15rpm or 20rpm, etc., which is not limited here.

[0108] In some embodiments, the oxidizing atmosphere includes air or oxygen.

[0109] In some embodiments, the gas flow rate of the oxidizing atmosphere is controlled to be 100 mL / min to 1000 mL / min, specifically 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min, 500 mL / min, 600 mL / min, 700 mL / min, 800 mL / min or 1000 mL / min, etc., which is not limited here.

[0110] In some embodiments, the temperature of the pre-oxidation treatment is 200°C to 400°C, and can be 200°C, 220°C, 250°C, 280°C, 300°C, 320°C, 350°C, 390°C or 400°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0111] In some embodiments, the heating rate of the pre-oxidation treatment is 0.5°C / min to 2.0°C / min; specifically, it can be 0.5°C / min, 1.1°C / min, 1.5°C / min, 1.8°C / min, 1.9°C / min or 2°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0112] In some embodiments, the holding time of the pre-oxidation treatment is 1 h to 5 h, specifically 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0113] It should be noted that controlling the various process parameters of the pre-oxidation treatment can accelerate the chemical cross-linking between polyamine compounds and asphalt molecules and between asphalt molecules, promote the transformation of some structures of the coating layer to disordered structures, and reduce the excessive surface pore structures caused by the rapid escape of small molecules during the carbonization process, improve the density of the coating, and reduce the occurrence of side reactions. The ordered structure of the amorphous carbon material in the coating layer has better conductivity and stronger binding force with the graphite core, reducing the surface contact resistance, while the disordered structure provides more lithium ion embedding channels, promotes lithium ion transmission, and improves the fast charging performance of the material at low coating amounts.

[0114] S20, carbonizing the precursor under a protective atmosphere to obtain a negative electrode material.

[0115] In some embodiments, the reaction temperature of the carbonization treatment is 800°C to 1500°C, specifically, it can be 800°C, 950°C, 1080°C, 1300°C, 1400°C or 1500°C, etc., but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. It can be understood that too high a carbonization treatment temperature may cause a decrease in the disorder of the amorphous carbon material, resulting in a decrease in the rate performance of the negative electrode material; when the carbonization treatment temperature is too low, the solidification and coking process of the precursor will be incomplete, resulting in a significant decrease in the conductivity of the amorphous carbon material formed by asphalt carbonization, a significant increase in product impedance, and too many groups on the surface of the coating layer, which significantly increases side reactions, resulting in a sharp deterioration in product performance.

[0116] It should be noted that during the carbonization process, polyamine compounds can chemically cross-link with short-chain molecules in solid asphalt to form long-chain molecules, and with the introduction of oxygen-containing groups and amino groups in polyamine compounds, part of the structure in the carbon material after carbonization will be transformed into a disordered structure with higher disorder and larger interlayer spacing, and a certain degree of nitrogen doping will be achieved. This nitrogen-doped ordered-disordered phase structure, while ensuring the electronic conductivity of the material surface, increases the lithium ion transmission channel and enhances the interaction between the material and lithium ions, accelerating the desolvation process and transmission of lithium ions during charging, thereby improving the fast charging performance of the material.

[0117] In some embodiments, the heat preservation time of the carbonization treatment is 1 hour to 10 hours, specifically, it can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours or 10 hours, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the heat preservation time of the carbonization treatment is 1 hour to 3 hours.

[0118] Optionally, the heating rate of the carbonization treatment is 0.5℃ / min to 5℃ / min, specifically 0.5℃ / min, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min or 5℃ / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0119] In some embodiments, the carbonization treatment is performed under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton and xenon.

[0120] In some embodiments, the gas flow rate of the protective atmosphere is 2 ml / s to 100 ml / s, specifically 2 ml / s, 5 ml / s, 10 ml / s, 15 ml / s, 20 ml / s, 30 ml / s, 50 ml / s, 60 ml / s, 70 ml / s, 89 ml / s or 100 ml / s, etc., which is not limited here.

[0121] In some embodiments, after the carbonization treatment, at least one of crushing, screening and demagnetization is further performed; preferably, after the carbonization treatment, crushing, demagnetization and screening are further performed in sequence.

[0122] In some embodiments, the crushing method is any one of a mechanical crusher, a jet mill and a low-temperature crusher.

[0123] In some embodiments, the screening method is any one of a fixed screen, a drum screen, a resonance screen, a roller screen, a vibrating screen and a chain screen, and the screening mesh number is 200 to 500 meshes. Specifically, the screening mesh number can be 200 mesh, 300 mesh, 400 mesh, 500 mesh, etc. The particle size of the negative electrode material is controlled within the above range, which is beneficial to the improvement of the processing performance of the negative electrode material.

[0124] In some embodiments, the demagnetization equipment is any one of a permanent magnetic drum magnetic separator, an electromagnetic iron remover and a pulsating high gradient magnetic separator. The demagnetization is to ultimately control the magnetic substance content of the negative electrode material, reduce the discharge effect of the magnetic substance on the lithium-ion battery and the safety of the battery during use.

[0125] In a third aspect, the present application provides a battery, wherein the battery comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.

[0126] Those skilled in the art will understand that the above-described method for preparing a lithium-ion battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.

[0127] The following is a further description of the embodiments of the present application in multiple embodiments. The embodiments of the present application are not limited to the following specific embodiments. Within the scope of protection, appropriate changes can be made to the implementation.

[0128] Example 1

[0129] The method for preparing the negative electrode material of this embodiment comprises the following steps:

[0130] (1) Take 1 part of solid asphalt with a softening point of 180°C and fully dissolve it in 100 parts of tetrahydrofuran solution, add 0.2 parts of polyetheramine, and stir and dissolve for 3 hours to obtain a coating solution.

[0131] (2) 125 parts of graphite were gradually added to the coating solution, stirred at room temperature for 1 hour, and then the temperature was adjusted to 80° C. for drying and tetrahydrofuran was recovered, and the mixture was dried to obtain a mixture.

[0132] (3) The mixture was transferred to a rotary kiln, and 300 mL / min of compressed air was introduced. The temperature was set to increase the temperature to 300 °C at 2 °C / min and keep it at that temperature for 3 h. The precursor was obtained after natural cooling.

[0133] (4) The precursor is carbonized in a carbonization kiln under a nitrogen atmosphere, the temperature is increased to 1150° C. at a heating rate of 5° C. / min, the heat preservation time is 4 h, and the negative electrode material is obtained by cooling.

[0134] Figure 3a This is a high-resolution transmission electron microscopy image of the negative electrode material provided in Example 1 of the present application, such as Figure 3a As shown, the negative electrode material includes graphite and an amorphous carbon material coating layer.

[0135] The performance parameters of the negative electrode material prepared in this example are shown in Table 1.

[0136] Example 2

[0137] Different from Example 1,

[0138] In step (1), the amount of asphalt added is 1.5 parts.

[0139] Example 3

[0140] Different from Example 1,

[0141] In step (1), the amount of asphalt added is 0.5 parts.

[0142] Example 4

[0143] Different from Example 1,

[0144] In step (3), the maximum temperature of the pre-oxidation treatment is set to 250°C.

[0145] Example 5

[0146] Different from Example 1,

[0147] In step (3), the maximum temperature of the pre-oxidation treatment is set to 350°C.

[0148] Example 6

[0149] Different from Example 1,

[0150] In step (3), the maximum temperature holding time of the pre-oxidation treatment is set to 1 hour.

[0151] Example 7

[0152] Different from Example 1,

[0153] In step (3), the maximum temperature holding time of the pre-oxidation treatment is set to 5 hours.

[0154] Example 8

[0155] Different from Example 1,

[0156] In step (1), the amount of polyetheramine added is 0.1 parts.

[0157] Example 9

[0158] Different from Example 1,

[0159] In step (1), the amount of polyetheramine added is 0.4 parts.

[0160] Example 10

[0161] Different from Example 1,

[0162] In step (1), the amount of polyamide added is 0.2 parts.

[0163] Embodiment 11

[0164] Different from Example 1,

[0165] In step (1), the amount of polyvinylamine added is 0.2 parts.

[0166] Comparative Example 1

[0167] (1) dissolving 1 part of solid asphalt with a softening point of 180°C in 100 parts of tetrahydrofuran solution, stirring and dissolving for 3 hours to obtain a coating solution;

[0168] (2) 125 parts of graphite are gradually added to the coating solution, stirred at room temperature for 1 hour, and then the temperature is adjusted to 80° C. to dry and recover tetrahydrofuran, and dry to obtain a mixture;

[0169] (3) The mixture was carbonized in a carbonization furnace under a nitrogen atmosphere, heated to 1150° C. at a heating rate of 5° C. / min, kept at the temperature for 4 h, and cooled to obtain the negative electrode material.

[0170] Comparative Example 2

[0171] (1) 2 parts of solid asphalt having a softening point of 160° C. and 100 parts of graphite are mixed to obtain a mixture;

[0172] (2) The mixture was carbonized in a carbonization furnace under a nitrogen atmosphere, the temperature was increased to 1150° C. at a heating rate of 5° C. / min, the heat preservation time was 4 h, and the mixture was cooled to obtain the negative electrode material.

[0173] Comparative Example 3

[0174] (1) 0.6 parts of solid asphalt having a softening point of 180° C. and 100 parts of graphite are mixed to obtain a mixture;

[0175] (2) The mixture was carbonized in a carbonization furnace under a nitrogen atmosphere, the temperature was increased to 1150° C. at a heating rate of 5° C. / min, the heat preservation time was 4 h, and the mixture was cooled to obtain the negative electrode material.

[0176] Comparative Example 4

[0177] Different from Example 1,

[0178] In step (1), the amount of polyetheramine added is 0.01 parts.

[0179] Comparative Example 5

[0180] Different from Example 1,

[0181] In step (1), the amount of polyetheramine added is 1 part.

[0182] Test Method

[0183] (1) Testing method for median particle size of negative electrode materials:

[0184] The particle size distribution range of the negative electrode material was tested by Malvern laser particle size analyzer.

[0185] (2) Test method for tap density of negative electrode materials:

[0186] Place the negative electrode material in the sample chamber of the tap density meter, vibrate it 1000 times, and record the sample volume at this time. The tap density can be calculated according to the mass-to-volume ratio.

[0187] (3) Testing method for specific surface area of ​​negative electrode material:

[0188] Under constant temperature and low temperature, after measuring the adsorption amount of gas on the solid surface at different relative pressures, the monolayer adsorption amount of the sample is obtained based on the Brownauer-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of ​​the material.

[0189] (4) Test method for compaction density of negative electrode materials:

[0190] The compaction density test was carried out using the national standard GB / T 24533-2009 test method for lithium-ion battery graphite negative electrode materials, with a test pressure of 5 tons.

[0191] (5) Thickness test of carbon coating layer of negative electrode material:

[0192] The surface morphology and thickness of the negative electrode material were characterized using a high-resolution transmission electron microscope (HRTEM, model: FEITitan 80-300 300KV).

[0193] (6) Raman testing of carbon materials:

[0194] Raman spectroscopy was measured using a Jobin Yvon LabRAM HR spectrometer with a light source of 532 nm and a test range of 0 cm -1 ~4000cm -1 .

[0195] (7) Disorder test of carbon materials:

[0196] The amorphous carbon material was observed by high-resolution transmission electron microscopy. Ten points of amorphous carbon material with a length of 100 nm parallel to the particle surface were randomly selected on the surface of the negative electrode material, and the lengths of the disordered structures therein were measured, which were recorded as: n1, n2, n3...n10 respectively. The calculation formula for the degree of disorder w is: w=(n1 / 100+n2 / 100+n3 / 100+...+n10 / 100) / 10.

[0197] (8) Test method for mass content of amorphous carbon material in negative electrode material:

[0198] Thermogravimetric analysis was used to test the mass content of amorphous carbon materials.

[0199] (9) Test of the mass content of nitrogen in negative electrode materials

[0200] The nitrogen content of the negative electrode material was measured using an ONH2000 oxygen and nitrogen element analyzer.

[0201] (10) Lithium-ion button cell half-cell rate performance test:

[0202] The negative electrode materials prepared in each embodiment and comparative example were respectively used as active materials, mixed in a mass ratio of active material: conductive carbon black: CMC: SBR = 95.3:1.5:1.4:1.8, mixed with deionized water as solvent and then coated on copper foil, with a coating surface density of 6.5±0.1 mg / cm 2 After vacuum drying at 90°C, the pole piece was obtained, and the pole piece was rolled to a compaction density of 1.50±0.02g / cc. The pole piece, lithium sheet, electrolyte (1mol / L LiPF6, EC:EMC:DMC=1:1:1) and Celgard2400 separator were assembled into a 2016-type button half-cell.

[0203] The button half-cell was tested for rate performance at 25±2℃, and the charge-discharge specific capacity and coulomb efficiency of 0.1C, 0.2C, 1C and 2C were obtained. Rate test conditions: ①0.1C discharge to 0.01V, constant voltage to 0.01C, 0.1C charge to 1.5V; ②0.2C discharge to 0.01V, constant voltage to 0.01C, 0.2C charge to 1.5V; ③1C discharge to 0.01V, constant voltage to 0.01C, 0.2C charge to 1.5V; ④2C discharge to 0.01V, constant voltage to 0.01C, 0.2C charge to 1.5V. The 1C / 0.2C discharge capacity retention rate can be calculated by dividing the 1C discharge specific capacity by the 0.2C discharge specific capacity.

[0204] (11) Lithium-ion full battery test:

[0205] The negative electrode material prepared in each embodiment was used as an active material, and was mixed in a mass ratio of active material: conductive carbon black: CMC: SBR = 95.3:1.5:1.4:1.8, mixed with deionized water as a solvent, and then coated on a copper foil, and vacuum dried at 90°C to obtain a negative electrode sheet; lithium iron phosphate, polyvinylidene fluoride and conductive agent carbon black were mixed in a mass ratio of 95:2:3 with solvent NMP (N-methylpyrrolidone), coated on a 16μm thick aluminum foil, and vacuum dried to obtain a positive electrode sheet; the coated positive and negative electrode sheets were subjected to sheet making, winding, drying, liquid injection, sealing, formation, volume separation and other processes to make a 554065 type soft-pack lithium-ion battery.

[0206] The obtained soft-pack battery was charged and discharged on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. at 45°C, with a current of 1C / 1C and a charge and discharge voltage limit of 3.0-4.35V. The first efficiency and 50-week capacity retention rate tests were performed (the compaction density of the negative electrode sheet was 1.55g / cm 3 );

[0207] The results of the above performance tests are as follows:

[0208] Table 1. Performance comparison results

[0209]

[0210]

[0211] According to the test data of Examples 1 to 11, the amorphous carbon material on the graphite surface has not only an ordered structure but also a disordered structure, presenting a chaotic graphite structure. The disorder degree of the amorphous carbon material is 0.05 to 0.08. The amorphous carbon material has more carbon structures perpendicular to the graphite surface, and the disorder degree value is relatively high, which is conducive to the embedding of lithium ions. The doping of nitrogen elements is conducive to enhancing the interaction between the carbon material and lithium ions, and promoting the desolvation process of lithium ions, thereby improving the rate performance of the material, and the capacity, first efficiency and high temperature performance of the material are significantly improved.

[0212] It can be seen from Example 1, Example 2 and Example 3 that when the coating amount of the carbon material is 0.2%, the performance of the negative electrode material is better.

[0213] According to Example 1, Example 4 and Example 5, the pre-oxidation temperature of Example 5 is too high, which may destroy part of the cross-linked molecular structure. The pre-oxidation temperature of Example 4 is too low, and the degree of polymer cross-linking on the graphite surface decreases, which in turn causes fluctuations in the disorder of the carbon material formed by carbonization. Preferably, the pre-oxidation temperature is 280°C to 320°C.

[0214] According to Example 1, Example 6 and Example 7, the pre-oxidation treatment time will also affect the degree of cross-linking of the polymer. In order to reduce excessive oxidation and excessive disorder, the pre-oxidation treatment time is preferably 2.5h to 3.5h, which is beneficial to comprehensively improve the rate performance of the negative electrode material.

[0215] According to Example 1, Example 8 and Example 9, the amount of polyamine compound added will also affect the degree of crosslinking of the polymer. In order to reduce the disorder degree, the mass ratio of graphite to polyamine compound is preferably 125: (0.2-0.3). It can be understood that the addition of polyetheramine affects the disorder value of the material. Too low disorder affects the transmission of lithium ions and is not conducive to the improvement of rate performance. Too high disorder leads to increased impedance on the surface of the material, a slight decrease in conductivity, which is not conducive to the improvement of rate performance, and a decrease in high temperature performance.

[0216] According to Example 1, Example 8 and Example 9, compared with polyamide, polyethyleneamine and polyetheramine, the nitrogen doping amount of the amorphous carbon coating layer is reduced and the disorder degree is increased, but the overall performance of the negative electrode material is slightly lower than that of the negative electrode material prepared by polyetheramine. This is because different polyamine compounds have different nitrogen contents and different degrees of crosslinking with asphalt molecules, which leads to different densities of the coating layer and thus different performance. Preferably, the polyamine compound is polyetheramine.

[0217] According to Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, when solid phase coating is used and the residual carbon is 1% (Comparative Example 2), the rate performance of the material is high, but the capacity and first efficiency of the negative electrode material are lost more, and the high temperature performance of the material is poor. After solid phase coating is used and the residual carbon is reduced to 0.2% (Comparative Example 3), the specific surface area of ​​the negative electrode material is larger, and the Raman value I D / I G The value is also low, indicating that solid phase coating is difficult to ensure the uniformity of coating, and the rate performance and high temperature performance of the material are poor.

[0218] According to Example 1, Comparative Example 4 and Comparative Example 5, the samples obtained by adding too little or too much polyamine compounds without pre-oxidation treatment have a relatively high specific surface area, and the defect degree of the amorphous carbon surface formed is higher and the density is insufficient, which affects the initial efficiency of the negative electrode material, and the capacity loss of the material is faster during high-temperature cycling, and the high-temperature performance is poor.

[0219] In Example 1 of the present application, after liquid phase coating, the Raman Id / Ig average value of the negative electrode material increased significantly, and the coating uniformity was improved. Figure 3a As shown, the amorphous carbon material on the surface of the graphite material presents an ordered structure and a disordered structure. The ordered structure is tightly combined with the graphite substrate and has good conductivity. The disordered structure has a wider carbon layer spacing, which is conducive to the rapid transmission of lithium ions. The comprehensive performance of the negative electrode material of the present application has been significantly improved. Figure 3bAs shown, the carbon material on the surface of the negative electrode material of Comparative Example 1 has only an ordered structure. Since the arrangement direction of the carbon layer is parallel to the graphite surface and perpendicular to the lithium ion embedding direction, it is not conducive to the transmission of lithium ions. Its disorder value is 0, and there is a large room for improvement in rate performance.

[0220] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material comprises a core and an amorphous carbon material located on at least a portion of the surface of the core, wherein the core comprises graphite, and the amorphous carbon material comprises an ordered structure and a disordered structure; wherein the disorder degree of the amorphous carbon material is 0.05 to 0.8; The disorder degree of the amorphous carbon material is obtained by the following test method: The negative electrode material was observed by high-resolution transmission electron microscopy, and 10 amorphous carbon materials with a length of 100 nm parallel to the particle surface were randomly selected on the surface of the negative electrode material. The lengths of the disordered structures therein were measured, and recorded as: n1, n2, n3...n10, respectively. The calculation formula of the disorder degree w is: w=(n1 / 100+n2 / 100+n3 / 100+...+n10 / 100) / 10.

2. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following characteristics: (1) The graphite includes at least one of artificial graphite and natural graphite; (2) The median particle size of the graphite is 5 μm to 10 μm; (3) The amorphous carbon material includes doped nitrogen; (4) The amorphous carbon material includes doped nitrogen, and the mass content of the doped nitrogen in the amorphous carbon material is 0.01% to 0.2%; (5) The amorphous carbon material is located on the surface of the graphite to form a carbon coating layer, and the thickness of the carbon coating layer is 5nm to 50nm; (6) The negative electrode material was determined by Raman spectroscopy at 1300 cm -1 ~1350cm -1 The peak area of ​​the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak within the range is I D / I G , 0.6≤I D / I G ≤1.

0.

3. The negative electrode material according to claim 1 or 2, characterized in that: The negative electrode material satisfies at least one of the following characteristics: (1) The median particle size of the negative electrode material is 5 μm to 10 μm; (2) The specific surface area of ​​the negative electrode material is 0.2 m 2 / g~3m 2 / g; (3) The tap density of the negative electrode material is 0.7 g / cm 3 ~1.2g / cm 3 ; (4) The compaction density of the negative electrode material under a pressure of 5T is 1.6 g / cm 3 ~2.0g / cm 3 ; (5) The mass percentage content of the amorphous carbon material in the negative electrode material is 0.05% to 0.3%.

4. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Adding graphite into a coating liquid for mixing and dispersion, and drying to obtain a mixture, wherein the coating liquid comprises solid asphalt with a softening point of ≥180°C, an organic solvent, and a polyamine compound; placing the mixture in an oxidizing atmosphere for pre-oxidation treatment to obtain a precursor; The precursor is carbonized to obtain a negative electrode material.

5. The preparation method according to claim 4, characterized in that: The negative electrode material satisfies at least one of the following characteristics: (1) The graphite includes at least one of artificial graphite and natural graphite; (2) The median particle size of the graphite is 5 μm to 10 μm; (3) The mass content of carbon in the graphite is ≥ 95%; (4) The coking value of the solid asphalt is 40% to 70%; (5) The organic solvent comprises one of tetrahydrofuran, quinoline, toluene, xylene, N-methylpyrrolidone and ethanol; (6) The mass ratio of the graphite, the solid asphalt, the organic solvent and the polyamine compound is 100: (0.1-1): (50-500): (0.01-0.4); (7) The polyamine compound includes at least one of polyetheramine, polyethyleneamine, polyethyleneimine, polyurethane, polyamide, polyacrylamide and polyimide.

6. The preparation method according to claim 4 or 5, characterized in that: The negative electrode material satisfies at least one of the following characteristics: (1) The solid asphalt comprises at least one of petroleum-based solid asphalt and coal-based solid asphalt; (2) The mixing and dispersing method includes at least one of mechanical stirring and ultrasonic dispersion; (3) The temperature of the drying process is greater than the boiling point of the organic solvent; (4) The drying temperature is greater than the boiling point of the organic solvent, and the difference is 5°C to 10°C; (5) The drying process is carried out under stirring.

7. The preparation method according to claim 6, characterized in that: The negative electrode material satisfies at least one of the following characteristics: (1) The pre-oxidation treatment is carried out in a rotary kiln, and the rotation speed of the rotary kiln is 2 rpm to 20 rpm; (2) The oxidizing atmosphere includes air or oxygen; (3) The gas flow rate of the oxidizing atmosphere is controlled to be 100 mL / min to 1000 mL / min; (4) The temperature of the pre-oxidation treatment is 200° C. to 400° C.; (5) The heating rate of the pre-oxidation treatment is 0.5°C / min to 2.0°C / min; (6) The pre-oxidation treatment is carried out for a holding time of 1 to 5 hours.

8. The preparation method according to claim 4 or 5, characterized in that: The method satisfies at least one of the following features: (1) The carbonization treatment is carried out under a protective atmosphere; (2) the carbonization treatment is carried out under a protective atmosphere, wherein the protective atmosphere comprises at least one of nitrogen, helium, neon, argon, krypton and xenon; (3) The temperature of the carbonization treatment is 800° C. to 1500° C.; (4) The heating rate of the carbonization treatment is 0.5°C / min to 5.0°C / min; (5) The heat preservation time of the carbonization treatment is 1h to 10h.

9. A battery, comprising the negative electrode material according to any one of claims 1 to 3 or the negative electrode material prepared according to the preparation method according to any one of claims 4 to 8.